(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: Survey the current status of antibiotic use in the treatment of community-acquired pneumonia in patients with non-small cell lung cancer in the elderly at Nghe An Oncology Hospital in 2024. Research methods: Prospective, cross-sectional description and analysis of each case. Research results: 85.3% of patients used antibiotics before admission; the average duration of antibiotic use was 8.3 ± 3.0 days. Piperacillin is the most used active ingredient (32.5%), followed by the Quinolone group of antibiotics, accounting for 51.9%, of which the antibiotic Moxifloxacin accounts for the highest proportion, 31.2%. Single-agent regimens account for 82%, of which Piperacillin is the most used active ingredient (24.6%). The combination regimen of two antibiotics, Ppiperacillin and Moxifloxacin, is the most used at a rate of 13.1%. In 77% of cases, the Ministry of Health’s guidelines selected antibiotic selection. Conclusion: The results show that choosing appropriate antibiotics and regimens to treat community-acquired pneumonia in elderly patients with non-small cell lung cancer is a decisive factor for doctors in successful clinical treatment. Emphasise the importance of monitoring and compliance with antibiotic use to improve effectiveness and limit antibiotic resistance.